2022
DOI: 10.3389/fonc.2022.960914
|View full text |Cite
|
Sign up to set email alerts
|

Atypical presentation of patients with chronic myeloid leukemia in chronic phase—Case report

Abstract: The presence of the translocation t(9;22)(q34;q11), leading to the BCR::ABL1 fusion transcript, is the hallmark of chronic myeloid leukemia (CML). Nevertheless, atypical presentation at diagnosis can be challenging. However, although most patients with CML are diagnosed with the e13a2 or e14a2 BCR::ABL1 fusion transcripts, about 5% of them carry rare BCR::ABL1 fusion transcripts, such as e19a2, e8a2, e13a3, e14a3, e1a3, and e6a2. In particular, the e6a2 fusion transcript has been associated with clinically agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
(39 reference statements)
0
0
0
Order By: Relevance
“…Several studies revealed that e6a2 BCR‐ABL1 transcript showed higher transforming capacity than major BCR‐ABL1 transcript and resistance to imatinib treatment. However, treatment with second‐generation TKIs, such as nilotinib, seems to result in a deep and enduring molecular remission 24 . CML patients with the e19a2 or e1a2 transcript were associated with inferior outcomes to TKI therapy, especially imatinib therapy, which might be recommended to receive second‐generation TKI as first‐line therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies revealed that e6a2 BCR‐ABL1 transcript showed higher transforming capacity than major BCR‐ABL1 transcript and resistance to imatinib treatment. However, treatment with second‐generation TKIs, such as nilotinib, seems to result in a deep and enduring molecular remission 24 . CML patients with the e19a2 or e1a2 transcript were associated with inferior outcomes to TKI therapy, especially imatinib therapy, which might be recommended to receive second‐generation TKI as first‐line therapy.…”
Section: Discussionmentioning
confidence: 99%